IMPLEMENTATION OF WEBSITE BASED E-MARKETING STRATEGY IN ORGANIC COCONUT SUGAR BUSINESS GROUP - Nur Chasanah; Ade Irma Anggraeni; Wita Ramadhanti; Aldila Krisnaresanti; Lina Rifda Naufalin; Aldila Dinanti (Jurnal Teknik Informatika (Jutif), 2022)
Coconut as one of the plantation commodities in Indonesia which has been processed into various products, one of which is organic coconut sugar. Organic Coconut sugar is one of Indonesia's natural products that has high competitiveness in the domestic and international markets. However, the fulfillment of the needs of the large organic coconut sugar market is still met not by direct producers but through various sales intermediaries. KUB Central Agro Lestari located in Purbalingga Regency is one of the producers of organic coconut sugar with a production capacity of over 200 tons/month. One way of marketing that has been taken by KUB Central Agro Lestari is to use a website to educate consumers about organic coconut sugar as well as a model for receiving orders from consumers. This study aims to implement an e-marketing strategy in the organic coconut sugar group, especially at KUB Central Agro Lestari. The method used in making this system is the waterfall method where this method has 5 stages, namely user needs analysis, system design, implementation, testing and maintenance. The results of the black-box test show valid results for all features which indicate that this website is as expected. From the results of black-box testing, it can be concluded that this website is appropriate to be used as a tool to implement e-marketing strategies at KUB Central Agro Lestari, Purbalingga.